(3dYdg JaSjQ GdHjVGhjs - (3eLghds
(3ChdgG (B:s
(3LYd GdTeS Ydjg OdjdG ahLH Medg Ydi GdeLGR HCf jLYd cdeI Ke GSJYGQI JHYjIs
(3BNQgG (B:s
(3MjK GMJbQg Hbhdg(B: (3Ndb ef Wjf ShQI GdfGRYGJs
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs